ANALYSIS OF BUYING INTEREST FROM FOLLOWERS ON INSTAGRAM FOOD BLOGGER - Ermawati Ermawati; Arif Siaha Widodo; Santi Budiman (MESP–FEB UNS, 2026)
The rapid growth of Instagram-based culinary marketing among MSMEs in Yogyakarta has highlighted the need for an empirically grounded framework that connects social media communication design with consumer purchase intention. However, no prior study has integrated the 5C framework (Context, Content, Community, Communication, Connection) with the consumer response hierarchy (Awareness, Knowledge, Liking, Preference, Conviction, Intention to Purchase) into a single structural model tested in a local culinary account context. This study employed a quantitative explanatory design using covariance-based Structural Equation Modeling (SEM) with LISREL software. Data were collected via an online questionnaire distributed to followers of the Nongkrong Jogja Instagram account using the Add Web Link feature, yielding 442 valid respondents. Of the 28 measurement indicators, 26 (92.86%) met validity and reliability criteria. Partially, 63.3% of individual 5C component hypotheses were rejected, indicating that no single component independently drives purchase intention. Simultaneously, however, all six composite hypotheses were accepted, with an average R² of 0.69, meaning the integrated 5C model explains approximately 69% of the variation in buying interest stages from awareness to intention to purchase. The findings confirm that the effectiveness of Instagram-based marketing communication emerges from the synergistic integration of all five components rather than from any single dimension. Practitioners are advised to adopt a holistic content strategy that activates all 5C elements simultaneously. Future research should expand the population scope and employ longitudinal designs to strengthen causal inference.